SAW Method In Determining Social Assistance Recipients At The Bandar Pasir Mandoge Subdistrict Office - Selvia Angreini; Yori Apridonal M; Amalia Amalia (Brilliance: Research of Artificial Intelligence, 2026)
This study aims to design and implement an information system to improve the efficiency and accuracy of data processing in organizational activities. The research was motivated by problems found in the existing system, where data management was still conducted manually, resulting in frequent errors, data redundancy, and delays in report generation. These limitations negatively affected the overall performance and decision-making process within the organization. To address these issues, a system was developed using a structured methodology that includes requirements analysis, system design, implementation, and testing. The proposed system integrates data processing, transaction management, and reporting into a single platform, enabling real-time data access and more effective information management. System testing was conducted using functional testing methods to ensure that all features operate according to user requirements and system specifications. The results show that the system successfully improves operational efficiency by reducing processing time, minimizing human error, and increasing data accuracy. Furthermore, the system provides timely and well-structured reports that support better and faster decision-making processes. Based on the evaluation results, it can be concluded that the developed system is feasible and effective in solving the identified problems. The implementation of this system is expected to enhance overall organizational performance and can be further developed by integrating additional features to meet future needs and technological advancements.